KAJIAN STRUKTUR KOMUNITAS MAKROZOOBENTHOS DI SUNGAI KUALA TUHA KECAMATAN KUALA PESISIR KABUPATEN NAGAN RAYA - Wanidar Wanidar; M. Ali Sarong; Irma Dewiyanti (Universitas Syiah Kuala, 2016)
A study of macrozobenthos comunity structure in Kuala Tuha river of Kuala Pesisir subdistrict Nagan Raya was conducted in November 2015 and Mei 2016. The purpose of this study was to determine comunity structure macrozobenthos including the spesies composition and subtrate texture, density, frequency of attendence and diversity. The method used in determining the station were purposive sampling method. In every station determined by six plot three in left river and three in right river, the data analysis of spesies composition were used percentage’s formula, density was used by density formula, frequency of attendance by frequency attendance formula and diversity by diversity index formula. The result in November 2015 showed that (1) spesies composition it was found 4 mollusca 1 spesies of bivalves 2 spesies gastropods and 1 spesies malacostraca (2) The density ranged from 375 ind/m2- 875 ind/m2 (3) The frequency of attendance ranged from 33.24%-55% (4) Diversity ranged from 1.46-1.53 (5) and substrate texture in location research is sandy clay, dust and dusty clay. In may 2016 the showed that (1) spesies composition it was found 8 mollusca, 6 spesies gastropods, 1 spesies bivalves, 1 spesies malacostraca (2) The density ranged from 34 ind/m2-51 ind/m2, (3) Diversity ranged from 2.60-2.78 (4) and frequency of attendance of all three stasions is 100%. The conclusion obtained were: (1) The type of gastropode in may 2016 was higher than November 2015 (2) The density in May 2016 was higher November 2015 (3) Frequency of attendance in May 2016 often, while the frequency of attendance in November 2015 rarely (4) The diversty in November 2015 was low while in May 2016 was moderate. Penelitian tentang Kajian Struktur Komunitas Makrozoobenthos di Sungai Kuala Tuha Kecamatan Kuala Pesisir Kabupaten Nagan Raya telah dilakukan pada bulan November 2015 dan Mei 2016. Tujuan penelitian ini adalah untuk mengetahui struktur komunitas makrozoobenthos yang meliputi komposisi jenis dan tipe substrat, kepadatan, frekuensi kehadiran dan keanekaragaman. Penentuan stasiun penelitian dilakukan dengan metode purposive sampling. Pada setiap stasiun ditentukan plot sebanyak 6 plot, 3 di sisi kiri sungai dan 3 sisi kanan sungai. Analisa data tentang komposisi jenis dihitung dengan menggunakan rumus komposisi jenis, kepadatan dengan rumus kepadatan, frekuensi kehadiran dengan rumus frekuensi kehadiran dan keanekaragaman dengan rumus indek keanekaragaman. Hasil penelitian bulan November 2015 menunjukkan (1) komposisi jenis ditemukan 4 spesies moluska terdiri dari, 1 spesies Bivalvia, 2 spesies Gastropoda dan 1 spesies malacostraca (2) Kepadatan berkisar 375 ind/m2-875 ind/m2, (3) Frekuensi kehadiran berkisar 33,24%-55,25%,(4) Keanekaragaman berkisar 1,46-1,53 (5) Tekstur substrat di lokasi penelitian adalah lempung pasir, debu dan lempung berdebu. Pada bulan Mei 2016 menunujukkan (1) komposisi jenis ditemukan 6 spesies moluska 6 spesies Gastropoda 1 spesies Bivalvia dan 1 spesies Malacostraca, (2) Kepadatan berkisar 34 ind/m2-51 ind/m2,(3) Keanekaragaman berkisar 2,60-2,78 (4) Frekuensi kehadiran dari ketiga stasiun adalah 100%. Kesimpulan adalah (1) Komposisi jenis Gastropoda bulan Mei 2016 lebih tinggi dari bulan November 2015, (2) Kepadatan bulan Mei 2016 lebih tinggi dibandingkan November 2015, (3) Frekuensi kehadiran bulan Mei sering pada bulan November 2015 jarang, (4) keanekaragaman November 2015 rendah, sedangkan pada bulan Mei 2016 sedang.